The influence of dispersing structure in multiple drawing on the plasticity of low‑carbon steel - V. P. Fetisov (Литьë и металлургия)
During repeated drawing of low‑carbon steel, the initial grain size of ferrite and the intensity of hardening affect the accumulation of defects in the crystal structure and the overall decrease in the plastic properties of cold‑formed wire. Minimizing the cell sizes and reducing the intensity of deformation hardening for a more dispersed initial structure maintain an increased relative contraction of fine‑grained steel after large total compressions. The increase in the tendency to harden coarse‑grained steel is accompanied by an increased decrease in the ductility of the wire during repeated drawing. Large total compressions increase the structural sensitivity of the relative constriction of low‑carbon wire.